Pengaruh Keputusan Investasi dan Struktur Modal terhadap Nilai Perusahaan pada Sektor Konsumsi Periode 2015 - 2019 - Yusdianto Yusdianto (CV. Syntax Corporation Indonesia, 2021)
This study aims to determine and analyze whether the effect of investment decisions and capital structure as well as the relationship company value process significantly affects stock prices in listed consumer industry sector companies. on the Indonesia Stock Exchange (IDX) in 2015-2019. The sampling method used comparative causal was purposive sampling and obtained a sample of 12 companies. The data used is secondary data, namely the financial statements of the Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. Descriptive statistical analysis, panel data regression analysis, classic assumption test, and hypothesis testing (multiple linear regression) are the testing techniques in this study. The results showed that the variable investment decisions and capital structure as well as the financing relationship between the company value significantly to stock prices. Taken together investment decisions and capital structure are significant to company value in the Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) in 2015 -2019